Integrating principles of military team development into family medicine education. (September 2019) - Dixon, Mark A; Williams-Wonnum, Sundonia J; Alley, Ebon S; Hyer, Steven M
The United States military is an organization composed of teams of various sizes and functions. The development of effective teams is comprised of several components: leadership, followership, training, and development of team traits. This article reviews the literature and military doctrines surrounding these components to establish a conceptual model of team development. This model is intended to summarize military team development principles and to facilitate team functioning and development within medical settings. Organizational values, leader attributes and competencies, and the role of team members are discussed.